Enhancement of Meditation Analgesia by Opioid Antagonist in Experienced Meditators. Issue 9 (November 2018) - May, Lisa M.; Kosek, Peter; Zeidan, Fadel; Berkman, Elliot T.
ABSTRACT: Objective: Studies have consistently shown that long-term meditation practice is associated with reduced pain, but the neural mechanisms by which long-term meditation practice reduces pain remain unclear. This study tested endogenous opioid involvement in meditation analgesia associated with long-term meditation practice. Methods: Electrical pain was induced with randomized, double-blind, cross-over administration of the opioid antagonist naloxone (0.15-mg/kg bolus dose, then 0.2-mg/kg per hour infusion dose) with 32 healthy, experienced meditation practitioners and a standardized open monitoring meditation. Results: Under saline, pain ratings were significantly lower during meditation (pain intensity: 6.41 ± 1.32; pain unpleasantness: 3.98 ± 2.17) than at baseline (pain intensity: 6.86 ±1.04, t (31) = 2.476, p = .019, Cohen's d = 0.46; pain unpleasantness: 4.96 ±1.75, t (31) = 3.746, p = .001, Cohen's d = 0.68), confirming the presence of meditation analgesia. Comparing saline and naloxone revealed significantly lower pain intensity ( t (31) = 3.12, p = .004, d = 0.56), and pain unpleasantness ( t (31) = 3.47, p = .002, d = 0.62), during meditation under naloxone (pain intensity: 5.53 ± 1.54; pain unpleasantness: 2.95 ± 1.88) than under saline (pain intensity: 6.41 ± 1.32; pain unpleasantness: 3.98 ± 2.17). Naloxone not only failed to eliminate meditation analgesia but also made meditation analgesia stronger. Conclusions: Long-term meditation practice does not rely on endogenous opioids to reduce pain. Naloxone's blockade of opioid receptors enhanced meditation analgesia; pain ratings during meditation were significantly lower under naloxone than under saline. Possible biological mechanisms by which naloxone-induced opioid receptor blockade enhances meditation analgesia are discussed. Abstract : Supplemental digital content is available in the text.